Human metapneumovirus associated pneumonia and severe bronchiolitis in a 9-month-old infant admitted to a Sri Lankan hospital - F Noordeen; JAAS Jayaweera; MLM Rayes (Sri Lankan Journal of Infectious Diseases, 2016)
Human metapneumovirus (hMPV) has been shown to cause acute respiratory tract infections (ARTI) in children since its first detection in 2001 in the Netherlands. Globally, hMPV accounts for 2-10% of childhood ARTI. hMPV associated ARTI has not been reported in Sri Lanka. We report a case of hMPV infection in a nine-month-old infant with respiratory illness admitted to the paediatric ward of the Anuradhapura Teaching Hospital.